Tactile and thermal perception test with textile materials used in uniforms (ModaPalavra e-periódico, 2020)
Workwear is worn to standardize wearers throughout theworkday, and theirtextile materials come in direct contactwith the skin. However, this type of clothing is oftenpurchased in large quantities and are made of economicallyviable textile materials for employers. When comfort is not apriority, the user may be adversely affected by prolongeduse of parts. This article investigates the user's perception oftactile comfort, which is the touch of the fabric on the skin,and the thermal perception or sensation of heat or coldcaused by the textile sample. The field trial was conductedwith 20 participants using five textile samples commonlyused on shirts, T-shirts, and trousers for general serviceworkwear and one for sportswear. Samples were tested inpairs between flat and knitted fabrics. The results indicatethe participants' preference for sportswear because it issofter and fresher to the skin.
Keywords: comfort; textile materials; workwear